1990
DOI: 10.1016/s0010-9452(13)80316-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-Examination of CPM Performance and Neglect in Lateralized Brain Injury

Abstract: The current study examines the effects of lateralized brain injury on Raven's Coloured Progressive Matrices (CPM) performance. Archival data on 106 unilateral brain-damage patients, 59 with right hemisphere damage and 47 with left, was utilized to examine four aspects of differential performance. Right brain-damaged subjects performed significantly lower than left brain-damaged subjects overall on the CPM. They also showed evidence of a higher incidence of and greater severity of hemi-neglect. After partiallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Although there are no known prior studies of the AER in children with differing Matrices scores, it is widely agreed that ability to solve visual matrix analogy problems depends, at least in part, on right hemispheric, especially parietal, systems. 27 34 Our findings, which appear to replicate across all stimulus states (Figure 1, rows 3–5; Table 2), are consistent with this hypothesis. That our Matrices data illustrate regions outside the parietal area (see Figure 1, row 3, right frontotemporal), is in accord with reports that right hemispheric lesions outside the parietal area can affect performance on these tasks.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although there are no known prior studies of the AER in children with differing Matrices scores, it is widely agreed that ability to solve visual matrix analogy problems depends, at least in part, on right hemispheric, especially parietal, systems. 27 34 Our findings, which appear to replicate across all stimulus states (Figure 1, rows 3–5; Table 2), are consistent with this hypothesis. That our Matrices data illustrate regions outside the parietal area (see Figure 1, row 3, right frontotemporal), is in accord with reports that right hemispheric lesions outside the parietal area can affect performance on these tasks.…”
Section: Discussionsupporting
confidence: 80%
“…Matrices, a visual analogy test, is presumed to depend in part upon the integrity of right hemisphere functions, relatively unrelated to reading ability. 27 34 In this way, we could evaluate whether any two-tone EP response difference was specific to reading disability or whether it might be a general deficit of neural processing associated with other forms of learning impairment as well.…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly visuospatial items comprise more than one third of the RCPM (Lezak, 1995). A number of investigators have noted that Subtest A performance tends to be associated with the function of the right (visuospatial) hemisphere, and Subtest B performance with the function of the left hemisphere (analogic reasoning) (Costa, 1976; Denes, Semenza, & Stoppa, 1978; Drebing et al, 1990; Zaidel, 1981; also Villardita, 1985, with a somewhat different scoring system). If the RCPM assesses visuospatial skills as well as logical reasoning capacities, as these several studies suggest, then the widely reported impairment in PD on the RCPM may indicate a visuospatial disorder or a dysfunction of reasoning ability or both.…”
mentioning
confidence: 99%
“…Other measures, such as Raven’s Coloured Progressive Matrices (Raven, 1965; Raven, Court, & Raven, 1984) and the Hooper Visual Organization Test (Western Psychological Services, 1983), were not included in this battery because past research has failed to consistently demonstrate that they are differentially sensitive to right hemisphere dysfunction (Boyd, 1981; Drebing, Takushi, Tanzy, Murdock, Stewart, & Majovsky, 1990; Wang, 1977). The three measures that were selected, however, tap the elementary components of visuospatial functioning (Kritchevsky, 1988), which include spatial constructional ability (e.g., the CFT); spatial mental operations, or mental rotation skills (e.g., BD); spatial perceptual skills, or the ability to analyze the orientation of stimuli and localize those stimuli in space (e.g., JLO); and spatial attentional skills, or the ability to attend to both the left and right hemispaces (all three measures).…”
Section: Methodsmentioning
confidence: 99%